Using fish behavior to design a fish pot: Black seabream (Spondyliosoma cantharus) case study - Méhault, Sonia; Morandeau, Fabien; Simon, Julien; Faillettaz, Robin; Abangan, Alexa; Cortay, Aurore; Kopp, Dorothée (Frontiers in Marine Science, 2022)
The French fishing industry is becoming increasingly environmentally aware and likely to adopt more sustainable fishing gears. As a result, fishers are showing a growing interest in sustainable fish pots. This experiment aimed to develop a fish pot concept specifically based on target species behavior in French coastal waters. First, the consultation led with fishers indicated the black seabream as the main species of interest. Then, the pot’s characteristics were defined to comply with fishing regulations. The conception process of the pot was led step-by-step by gradually testing a pot design appropriated to black seabream’s natural behavior. The approach and feeding behaviors of black seabream were described using underwater video combined to an ethogram. The experiment led to a prototype of fish pot, which provide fishers with an innovative fishing gear.